Reducing the Soleus Stretch Reflex With Conditioning: Exploring Game- and Impedance-Based Biofeedback - van 't Veld, Ronald C.; Flux, Eline; Schouten, Alfred C.; van der Krogt, Marjolein M.; van der Kooij, Herman; van Asseldonk, Edwin H. F. (Frontiers in Rehabilitation Sciences, 2021)
People with spasticity, i.e. stretch hyperreflexia, have a limited functional independence and mobility. While a broad range of spasticity treatments is available, many treatments are invasive, non-specific or temporary and might have negative side effects. Operant conditioning of the stretch reflex is a promising non-invasive paradigm with potential long-term sustained effects. Within this conditioning paradigm, seated participants have to reduce the mechanically elicited reflex response using biofeedback of reflex magnitude quantified using electromyography (EMG). Before clinical application of the conditioning paradigm, improvements are needed regarding the time-intensiveness and slow learning curve. Previous research has shown that gamification of biofeedback can improve participant motivation and long-term engagement. Moreover, quantification of reflex magnitude for biofeedback using reflexive joint impedance may obtain similar effectiveness within fewer sessions. Nine healthy volunteers participated in the study, split in three groups. First, as reference the 'Conventional' group received EMG-, bar-based biofeedback similar to previous research. Second, we explored feasibility of game-based biofeedback with the 'Gaming' group receiving EMG-, game-based biofeedback. Third, we explored feasibility of game- and impedance-based biofeedback with the 'Impedance' group receiving impedance-, game-based biofeedback. Participants completed 5 baseline sessions (without reflex biofeedback) and 6 conditioning sessions (with reflex biofeedback). Participants were instructed to reduce reflex magnitude without modulating background activity. The Conventional and Gaming groups showed feasibility of the protocol in 2 and 3 out of 3 participants, respectively. These participants achieved a significant Soleus short-latency (M1) within-session reduction of at least -15% in the 4th to 6th conditioning session. None of the Impedance group participants showed any within-session decrease in Soleus reflex magnitude. The feasibility of the EMG-, game-based biofeedback calls for further research on gamification of the conditioning paradigm to obtain improved participant motivation and engagement, while achieving long-term conditioning effects. Before clinical application, the time-intensiveness and slow learning curve of the conditioning paradigm remain an open challenge.